History and Institutions Implementing Islamic Religious Education in Indonesia - A. Khuzainol Mubarok; Saiful Hadi; Achmad Anshari (Kasyafa: Jurnal Pendidikan Agama Islam, 2026)
This article discusses the institutional roles and coordination in implementing Islamic Religious Education (PAI) in Indonesia. Using a qualitative approach through library research, the study examines the roles of the Ministry of Religious Affairs (Kemenag), the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), and educational institutions in managing PAI. The findings reveal that the dual authority between Kemenag and Kemendikbudristek often leads to overlapping policies in teacher management, curriculum design, and learning evaluation. To address this issue, stronger institutional synergy is needed through a national coordination forum and the reinforcement of regulations that clearly define institutional responsibilities. Such synergy is expected to create an integrated and effective Islamic education system that harmonizes spiritual and intellectual aspects, ensuring PAI contributes to developing knowledgeable, faithful, and morally upright generations aligned with national education goals.